Field Observations during the Eleventh Microwave Water and Energy Balance Experiment (MicroWEX-11): from April 25, 2012, through December 6, 2012 - Tara Bongiovanni; Pang-Wei Liu; Karthik Nagarajan; Daniel Preston; Patrick Rush; Tim H.M. van Emmerik; Robert Terwilleger; Alejandro Monsivais-Huertero; Jasmeet Judge; Susan Steele-Dunne; Roger De Roo; Ruzbeh Akbar; et al. (EDIS)
This new report from UF/IFAS researchers provides another set of observation data that can be used to develop better models for accurate prediction of weather and near-term climate. It describes the observations conducted during the MicroWEX-11, a season-long experiment incorporating active and passive microwave observations for bare soil, elephant grass, and sweet corn using a variety of sensors to understand land–atmosphere interactions and their effect on observed microwave signatures. These observations match that of satellite-based passive microwave radiometers and NASA’s recently launched Soil Moisture Active Passive (SMAP) mission. This 96-page report was written by Tara Bongiovanni, Pang-Wei Liu, Karthik Nagarajan, Daniel Preston, Patrick Rush, Tim H.M. van Emmerik, Robert Terwilleger, Alejandro Monsivais-Huertero, Jasmeet Judge, Susan Steele-Dunne, Roger De Roo, Ruzbeh Akbar, Ella Baar, Max Wallace, and Anthony England and published by the UF Department of Agricultural and Biological Engineering, July 2015.